Evaluation of dental restorations: a comparative study between clinical and digital photographic assessments - Moncada, Gustavo; Silva, Francisco; Angel, Pablo; Oliveira Júnior, Osmir Batista de [UNESP]; Fresno, Maria Consuelo; Cisternas, Patricia; Fernández, Eduardo; Estay, Juan; Martin, Javier (Operative Dentistry, 2014)
The aim of this study was to compare the efficacy of a direct clinical evaluation method with an indirect digital photographic method in assessing the quality of dental restorations. Seven parameters (color, occlusal marginal adaptation, anatomy form, roughness, occlusal marginal stain, luster, and secondary caries) were assessed in 89 Class I and Class II restorations from 36 adults using the modified US Public Health Service/Ryge criteria. Standardized photographs of the same restorations were digitally processed by Adobe Photoshop software, separated into the following four groups and assessed by two calibrated examiners: Group A: The original photograph displayed at 100%, without modifications (IMG100); Group B: Formed by images enlarged at 150% (IMG150); Group C: Formed by digital photographs displayed at 100% (mIMG100), with digital modifications (levels adjustment, shadow and highlight correction, color balance, unsharp Mask); and Group D: Formed by enlarged photographs displayed at 150% with modifications (mIMG150), with the same adjustments made to Group C. Photographs were assessed on a calibrated screen (Macbook) by two calibrated clinicians, and the results were statistically analyzed using Wilcoxon tests (SSPS 11.5) at 95% CI. Results: The photographic method produced higher reliability levels than the direct clinical method in all parameters. The evaluation of digital images is more consistent with clinical assessment when restorations present some moderate defect (Bravo) and less consistent when restorations are clinically classified as either satisfactory (Alpha) or in cases of severe defects (Charlie). Conclusion: The digital photographic method is a useful tool for assessing the quality of dental restorations, providing information that goes unnoticed with the visual-tactile clinical examination method. Additionally, when analyzing restorations using the Ryge modified criteria, the digital photographic method reveals a significant increase of defects compared to those clinically observed with the naked eye. Photography by itself, without the need for enlargement or correction, provides more information than clinical examination and can lead to unnecessary overtreatment.
Keywords: Dental Restorations; Avaluation; Clinical assessments; Digital photographic